2008
DOI: 10.1007/s12011-008-8220-x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Selected Essential and Non-essential Elements in Blood of Harbor Seal (Phoca vitulina) Pups of the German North Sea

Abstract: This study on harbor seal (Phoca vitulina) pups of the North Sea evaluated concentrations of 14 essential and non-essential elements (Al, As, Be, Ca, Cd, Cr, Fe, Mn, Mo, Ni, Pb, Se, Sn, and Zn) in whole blood samples. The essential elements are analyzed to give references for health status determinations of pups. The measurement of classic toxic metals, like Pb or Cd, and other elements that may be in toxic concentrations in blood, is important due to their influence on health, particularly on the immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
4
9
0
1
Order By: Relevance
“…Furthermore, the concentrations of Pb and Sr also showed differences between samples of Elbe seals and animals of other Wadden Sea areas. Pb concentrations in blood of Elbe seals were similar to concentrations measured in seal pups found along the coasts of Schleswig-Holstein and seals from the island Römö, whereas seals caught on the Lorenzenplate revealed lower Pb concentrations (Griesel et al, 2008;Kakuschke et al, 2009). Stavros et al (2008) suggested that Pb concentrations in blood of Florida manatees may be caused by increased Pb concentrations transported via rivers.…”
Section: Element Profile In Whole Blood Samplessupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, the concentrations of Pb and Sr also showed differences between samples of Elbe seals and animals of other Wadden Sea areas. Pb concentrations in blood of Elbe seals were similar to concentrations measured in seal pups found along the coasts of Schleswig-Holstein and seals from the island Römö, whereas seals caught on the Lorenzenplate revealed lower Pb concentrations (Griesel et al, 2008;Kakuschke et al, 2009). Stavros et al (2008) suggested that Pb concentrations in blood of Florida manatees may be caused by increased Pb concentrations transported via rivers.…”
Section: Element Profile In Whole Blood Samplessupporting
confidence: 69%
“…Furthermore, several Ca concentrations measured in this study were higher compared to our previous studies on free ranging seals (Griesel et al, 2008). However, the concentrations were comparable to those measured in harbor seal pups (Kakuschke et al, 2009). TABLE 3.…”
Section: Element Profile In Whole Blood Samplessupporting
confidence: 66%
“…При этом рентгеновские спектрометры с дисперсией по энергии применялись авторами работ [52-56, 61, 72, 75, 81, 88, 91-94, 98-100, 102]; с волновой дисперсией [64,78,89,97]; с полным внешним отражением [57-60, 62, 63, 65, 67, 69-71,73, 74, 76, 77, 79-81, 83-87, 90, 95, 96, 103] и возбуждение синхротронным излучением в [66,68,82,96]. При выполнении некоторых исследований используют несколько методов [61,86,88,93,94,99,102] и реже несколько вариантов РФА [81].…”
Section: применение рфа для исследования жидкостей организмаunclassified
“…Therefore, reference intervals are a critical diagnostic tool used in the care of stranded animals and for population health investigations. In marine mammals from natural colonies, the information about essential elements in blood fractions is limited, and most reports refer to whole blood [1,[3][4][5][6].…”
mentioning
confidence: 99%